2019
DOI: 10.12927/cjnl.2019.25814
|View full text |Cite
|
Sign up to set email alerts
|

Violence Prevention: Technology-Enabled Therapeutic Intervention

Abstract: Recent estimates suggest that in Canada, over one-quarter of incidents of violent victimization occurred in the victim's place of work (Perreault 2015). Given the crisis-oriented nature of hospital care, healthcare workers disproportionately experience workplace violence (Perreault 2015). Nurses often interact with patients and family members under stressful situations, which can increase the risk of violence (Koller 2016). One study revealed that as many as a third of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Similar to other studies (e.g., Burkoski et al, 2019;Paterson et al, 2019), we found several gaps in flagging policy and procedures. Some gaps were particularly frustrating that, according to one manager, led workers to not comply with the policy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to other studies (e.g., Burkoski et al, 2019;Paterson et al, 2019), we found several gaps in flagging policy and procedures. Some gaps were particularly frustrating that, according to one manager, led workers to not comply with the policy.…”
Section: Discussionsupporting
confidence: 89%
“…Four of the five hospitals had a formal flagging policy and procedures, and in general, participants expressed positive views about flagging similar to other studies (e.g., Burkoski et al, 2019;Paterson et al, 2019). One hospital did not meet our criteria for inclusion because they did not have a flagging policy at all, despite legislation requiring measures and procedures to communicate personal information about a person's HOVB.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Some studies identified strategies to manage and prevent WPV episodes at different levels. For instance, allocating considerable funds to the prevention and management of WPV (Morphet et al, 2019 ), increasing staff numbers to prevent and manage WPV (Morphet et al, 2018 ), developing guidance materials evidence‐based, focusing on education and training of staff to manage WPV (Geoffrion et al, 2020 ), implementing monitoring, responding and reporting systems (Burkoski et al, 2019 ; Ramacciati et al, 2021 ), sharing information between health services and other agencies and improving communication abilities (Collins, 2021 ) and implementing an effective security staff (Morphet et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%